Analisis Peak Ground Acceleration (PGA) dan Intensitas Gempabumi berdasarkan Data Gempabumi Terasa Tahun 1981 - 2014 di Kabupaten Bantul Yogyakarta - Nugroho Budi Wibowo; Juwita Nur Sembri (Department of Physics, Sebelas Maret University, 2016)
Seismic historical record in Java period of 1981-2014 recorded that the Special Region of Yogyakarta was hit by damaging earthquake 4 times and hundreds of small earthquakes felt. This research was aimed to assess the peak ground acceleration (PGA) zone and the earthquake intensity based on historical data of earthquake occurrence in 1981-2014. Peak Ground Acceleration was calculated using Kanai equation and earthquake intensity using Wald equation. This research was conducted by using 231 microtremor data in Bantul District that derived from BMKG and also 147 data of damaging earthquake and small earthquake felt from BMKG. The result of this study represent peak ground acceleration value in Bantul District which was varied from 57.7-412.7 gal. Peak Ground Acceleration Zonation of Bantul District was diveded by 3 zones; first zone with PGA value 57.7-91 gal, the second zone with PGA value 92-179 gal and the third zone with PGA value higher than 180 gal. While based on earthquake intensity, Bantul District has damage potential of V-VII MMI in intensity scale.